Between Memory and Desire: The Middle East in a Troubled Age by R. Stephen Humphreys, (Berkeley: University of California Press, 1999, p. 297.) (American Journal of Islam and Society, 2001)
Between Memory and Desire is a joy to read, since it does justice to manymisunderstood subjects about Islam and the Middle East. Humphreys'genuine effort to be objective saves him from dismissing the reality of thephenomenon he is observing with his subjective redefinition of it.Being objective need not involve giving up one's set of values: it is neitherdesired nor possible not to have any values. Rather, objectivity is frankly toadmit that we do have values through which we respond to what weobserve. Because the author does this, he quite successfully compares andcontrasts his own point of reference, i.e. contemporary American values,with Islamic values. Humphreys' discussion not only will help theoutsiders understand Islam and Middle Eastern phenomenon better, butalso will enable the "insiders" to view how things look from outside anddo self-criticism.In the first chapter, Hard Realities: Population Overgrowthand Economic Stagnation, the author considers the difficult economicsituation of the Middle East. Humphreys notes that powerful market forcesof the first world have negative impact on the Middle Eastern economy,an effect persisting from colonial times. This point could have beenemphasized more, for the impact of the global capitalist economy on the ...